STUDI PENATALAKSANAAN TERAPI PADA PENDERITA HIV/AIDS DI KLINIK VCT RUMAH SAKIT KOTA MANADO - Kalalo,, Jef Gishard; Tjitrosantoso, Heedy; Goenawi, Lily Ranti (PHARMACON, 2012)
HIV (human immunodeficiency virus) is the virus that causes AIDS (aquiredimmunodeficiency syndrome) and AIDS is a condition when the lymphocytes and whiteblood cells were damaged thereby weakening the body's natural defense system. NationalAIDS Commission (KPA) of North Sulawesi Province notify the data cumulative basisJanuary - December 2011 HIV / AIDS in North Sulawesi is a 1.928 case. This study aimedto investigate the characteristics of people with HIV / AIDS in VCT Clinics Hospital in thecity of Manado and reviewing management of therapy in patients with HIV / AIDS in VCTClinics Hospital in the city of Manado with Free Clinical Management of HIV Infection inAdults and Adolescents those used by the Guidelines National Antiretroviral Therapy in2007 from the Ministry Of Health.This study is a descriptive survey research and data collection as retrospective for3 months from June to August 2012 at the VCT Clinic Hospital that is in Manado city thathas a special clinic VCT (Voluntary Counseling and Test). The study was conducted on 71records medical records of HIV / AIDS and got Antiretroviral therapy (ARV). Data wereanalyzed with descriptive analysis. The results showed 4 ARV drug regimen where thereare 32 patients (45.07%) got Main Line (Duv-Nev) and there were 17 patients (23.94%)got Line Alternative I (Duv-Efv) there are also 9 patients (12, 67%) got Alternative line II(Stav-Hiv-Nev) and 13 patients (18.30%) got Alternative line III (Stav-Hiv-Efv).Keywords: HIV, AIDS, VCT clinics and ARV